Certain Geometric Properties of the Canonical Weierstrass Product of an Entire Function Associated with Conic Domains - K. A. Selvakumaran; P. Rajaguru; S. D. Purohit; D. L. Suthar (Journal of Function Spaces)
In this paper, we determine the radius of λ-uniform convexity, λ-starlikeness, and α-convexity of order δ for the Weierstrass canonical product of an entire function as a root having smallest modulus and argument ϕ of a functional equation. As special cases, we also determine the radius of λ-uniform convexity, λ-starlikeness, and α-convexity of order δ for the entire function 1/Γ.